Inventory strategies for perishable products with two-period shelf-life and lost sales. Issue 17 (2nd September 2021) - Chen, Kebing; Xiao, Tiaojun; Wang, Shengbin; Lei, Dong
Abstract : We develop an inventory model for perishable products with a two-period shelf-life. The demand during a stock out in either period is treated as lost sales. Besides the initial regular order, the manager also has an opportunity to adjust the mid-cycle inventory with either expedited order or returns. An expedited order plan allows the manager to place an emergency order if the mid-cycle leftover inventory is low, while a returns plan offers the manager a chance to return some units within the validity period to suppliers if the leftover inventory is high. We show that both adjustment plans have their own thresholds, which exhibit a similar policy to that in the classical newsvendor model. Due to the dynamics of inventory, we investigate how the regular order is affected by each adjustment plan. Our findings indicate that the expedited order plan has a better performance in controlling the wastage risk, but it results in a higher shortage risk than the returns plan. Considering the respective advantages of the two plans, we show the existence of a new plan that is the combination of the two and justify the motivation for the manager to use it in the perishable inventory management.